Best Host Age of Anastrepha obliqua (Diptera: Tephritidae) for Multiplication of Four Native Parasitoids from the Americas. Issue 2 (29th March 2018) - Poncio, S; Montoya, P; Cancino, J; Nava, D E
Abstract: The success of the mass rearing of parasitoids is directly related to host quality, and it requires selecting the best biological host age to ensure the optimal performance of the parasitoids released into the field. The larval development of the parasitoids Utetes anastrephae (Viereck) (Hymenoptera: Braconidae) and Odontosema anastrephae Borgmeier (Hymenoptera: Eucoilidae) and the pupal development of the parasitoids Coptera haywardi (Ogloblin) (Hymenoptera: Diapriidae) and Dirhinus sp. (Hymenoptera: Chalcididae) on the native host Anastrepha obliqua (Macquart) (Diptera: Tephritidae) in different larvae and pupae ages were investigated under laboratory conditions. Not all parasitoid species developed with the same efficiency in immature individuals of A. obliqua ; U. anastrephae and C. haywardi showed the higher parasitism rates. The emergence and parasitism of U. anastrephae were equal using larvae from 5 to 8 d, while C. haywardi reared in 1- to 8-d-old pupae showed higher averages of parasitism. These results suggest that native parasitoids can be used to strengthen the implementation of biological control projects against A. obliqua, a pest of economic importance in South America.